Analisis Faktor-faktor yang Mempengaruhi Persepsi dan Partisipasi Masyarakat dalam Program Pemulihan Ekosistem Tahura Orang Kayo Hitam - Br Ginting, Nurhikmah Mila; Marwoto, Marwoto; Fazriyas, Fazriyas (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study analyzes the factors influencing community perception and participation in the ecosystem restoration program of Orang Kayo Hitam Forest Park (Tahura). Employing a mixed-methods approach, the research combines quantitative surveys (n=300) with in-depth interviews (n=30) of community members surrounding the Tahura. Exploratory factor analysis identified five main factors affecting community perception: ecological knowledge, socio-economic benefits, institutional trust, social norms, and previous conservation experience. Regression and path analyses revealed a significant relationship between perception and levels of community participation. The study underscores the importance of a holistic approach to community-based conservation area management, considering ecological, socio-economic, and institutional aspects. Practical implications include the development of environmental education programs, sustainable economic incentive schemes, and co-management systems that involve communities throughout the entire Tahura management cycle.